The Mad Monk: Sir Keith Joseph, Thatcherism, and the Morphology of Conservatism - Himsworth, Joseph (2022)
Via a morphological approach to the study of ideologies of the kind advocated by Michael Freeden, this thesis analyses the political thought of the British Conservative MP and leading Thatcherite, Sir Keith Joseph (1918-1994). It does so, as its title implies, in order to probe two interrelated issues - both Thatcherism as a form of conservatism and conservatism as an ideology. The four main chapters which comprise this document contend that, if Joseph was a Thatcherite, then Thatcherism is best considered as not a liberal ideology but a conservative one. Ideologies on this thesis’ account are modular structures comprised of political concepts, and conservatism is an anti-rationalist ideology which prioritises two concepts in particular – those being organic change and the extra-human origins of any social order – and which emerges in response to the threats posed by such rationalist ideologies as socialism and liberalism to those two core concepts. Beside the latter pair, the concepts that any one conservative favours are simply those that are most expedient then and there to defending organic change and society’s extra-human origins as that conservative perceives them. This thesis argues that this was true in Joseph’s ideology of, for example, Sir Keith’s epistemology, inequality, freedom, and the market, all of which Joseph defended as a means to shoring up that which was natural (extra-human) and the (organic) change which those extrahuman origins provided for. Conservatism is thus dialectical in nature. In arguing as much, this thesis validates Freeden’s description of conservatism. But the present author judges that this argument also has interesting implications for our comprehension of the 1970s as a political interregnum wherein new possibilities emerged. Thus this thesis emphasises the contingency of actually-existing Thatcherism and the gap between that practice and the political thought of a Thatcherite like Sir Keith Joseph.